Inflation Expectation Dynamics: A Structural Long-run Analysis for Turkey - Aykaç Alp, Elçin; Biyik, Zeynep (International Journal of Economics and Financial Issues, 2018)
This study analyses the relationship between inflation and inflation expectations for the period from 2006 to 2017 with monthly data for Turkey. We used current month inflation expectations, inflation expectations for one month ahead and inflation expectations for two month ahead. Those three expectations give us the chance to understand the effect of time on expectations and also understand how well the economic agents generate or change their expectations in time. We used TAR-VEC model for testing the long run relationship between the variables that we take into consideration. This method is selected because of the threshold structure of variables in this analyzing period. Our empirical findings show that inflation has positive effect on inflation expectations for current month. However expected inflation values for one and two month ahead are effected negatively from inflation realizations. Keywords: Inflation, inflation expectations, TAR-VEC model JEL Classifications: C32, E31